Aneurysmal bone cyst: a review - Elham Nasri; John David Reith (Korean Society of Pathologists & the Korean Society for Cytopathology, 2023)
Aneurysmal bone cyst (ABC) is a benign locally destructive bone neoplasm composed of multi-loculated blood-filled cystic spaces. The most common sites of involvement are the meta-diaphysis of the long bones and posterior elements of the vertebrae. Secondary, ABC-like changes can complicate a variety of other benign and malignant primary bone neoplasms, including giant cell tumor, fibrous dysplasia, and osteosarcoma. About two-third of primary ABCs have a rearrangement of the USP6 gene, which is not present in the ABC-like changes that occur secondary to other primary bone tumors (i.e., secondary ABC). Primary ABC of bone carries a variable but generally high rate of local recurrence. This paper provides an overview of the pathophysiology, clinical presentation, radiographic and pathologic findings, treatment, and prognosis of ABC.